Personal development program for skills development social in high school students - Rosales Llontop, Renée (2020)
The educational system has structured and organized each one of the aspects to be developed for the integral formation of the students in the secondary level, within them it considers the development of social skills, as part of the profile to be achieved in the students of this level, Applying various strategies. In this context, the present study aims to determine the effects of the personal development program for the development of the social skills of secondary school students. The study was applied, pre experimental design. The population was constituted by 782 and the sample by 636 students of the public educational institutions that belong to the UGEL N ° 1 of San Juan de Miraflores. Data collection was carried out in two questionnaires, validated by the trial of 05 experts, with a reliability of 0.7. The results of the personal development program in the development of social skills were significant according to the Cohen index: In assertiveness an average effect was achieved with 0.49, a medium effect was communicated with 0.38 and a large effect was made with 0.69.